Measurement of salicylic acid in human serum using stable isotope dilution and gas chromatography–mass spectrometry - Battezzati, A.; Fiorillo, G.; Spadafranca, A.; Bertoli, S.; Testolin, G. (Analytical biochemistry, 2006)
A simple, highly selective, and sensitive method using stable isotope dilution and gas chromatography–mass spectrometry has been developed to quantify salicylic acid (SA) at concentrations naturally occurring in biological fluids, such as in the serum of subjects not taking aspirin. After extraction of liquid–liquid with diethyl ether and ethyl acetate and preparation of the tert-butyldimethylsilyl derivative, SA content was detected using deuterated SA as internal standard. The mean recovery of SA from serum was 85 ± 6%. Intra- and interday precision and % relative error were <15% in all cases.With a detection limit of 0.6 ng and a quantification limit of 2 ng, the method is therefore also adequate for population studies because of the small amount of blood necessary to perform the analyses.